2003
DOI: 10.1007/s00383-003-1060-z
|View full text |Cite
|
Sign up to set email alerts
|

Childhood femoral hernia: a commonly misdiagnosed condition

Abstract: Femoral hernia is a rare surgical entity in the paediatric age group. The diagnosis is still a challenging issue. The aim of our study was to review our experience with femoral hernias in children during the past 21 years. We reviewed retrospectively the medical records of all patients who underwent femoral hernia repair in our institution between 1980 and 2000. Thirty-eight children (20 females, 18 males) with the median age of 5.5 years underwent 42 femoral hernia repairs over a 21-year period. Correct preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 14 publications
5
25
0
Order By: Relevance
“…Possibly the first description of FH in children is found in Sir Astley Paston Cooper's report of 2 girls with FH in 1827 [6,12,19].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Possibly the first description of FH in children is found in Sir Astley Paston Cooper's report of 2 girls with FH in 1827 [6,12,19].…”
Section: Discussionmentioning
confidence: 95%
“…Because of its rarity, misdiagnosis occurs in more than half of the cases [3,12]. Some FHs are diagnosed pre-or perioperatively, but an important number is discovered only at the time of groin hernia "recurrence" [4,9,12].…”
mentioning
confidence: 98%
“…It has been shown that with open surgery, femoral hernias are diagnosed correctly in only 53%, and that the recurrence rate is 13% [10]. With laparoscopy, the correct diagnosis is straightforward [11].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond detection of PPV, the laparoscopic approach of hernia repair has additional advantages over open hernia repair as it is also helpful in detecting direct, femoral, and combined hernias [8,9]. Another advantage of this technique is that vas deferens and spermatic vessels are not dissected (especially useful when dealing with a case of recurrent hernia following either open or previous laparoscopic repair).…”
Section: Discussionmentioning
confidence: 99%